Antimicrobial Activity of Silver-Zeolite LTA on Heavily-Contaminated Underground Ghanaian Waters - B. Kwakye-Awuah (International Journal of Science and Society, 2021)
Zeolite LTA was synthesized in the laboratory and loaded with silver ions by isomorphous substitution technique. The silver-loaded zeolite A (Ag-LTA) was characterized by X-ray diffraction (XRD) analysis, scanning electron microscopy (SEM), energy dispersive X-ray (EDX) and Fourier transformed infrared (FTIR) spectroscopy. XRD and SEM analysis showed little or no changes in the phase purity of all zeolites before and after ion exchange or before and after substitution of silver ions. The antimicrobial activity of the silver-loaded zeolite A was investigated by exposing well water samples from Vui community in the Volta Region of Ghana. Parameters such pH, conductivity and temperature as well as microbial analysis were measured before and after addition of silver-